The pick of the litter - Wallace, Bill, 1947- (New York : Holiday House, 2005)
Twelve-year-old Tom learns first-hand about honor, first when he is wrongly accused of lying at school, then when he faces the risk of losing a puppy he has come to love while helping his grandfather train hunting dogs, but writing to a new friend helps him sort his feelings and do the right thing.
680
Accelerated Reader AR
Keywords: Conduct of life -- Fiction; Pointer (Dog breed) -- Fiction; Dogs -- Training -- Fiction; Grandfathers -- Fiction; Letters -- Fiction